Characterization and classification of soils in the irrigable land of Achewa small-scale irrigation area, Itang special district, southwest Gambella, Ethiopia - Mengiste, Wasihun; Tsegaye, Dereje; Dagalo, Samuel; Yitbareke, Teshome (Frontiers in Soil Science, 2025)
The characterization and classification of soils in irrigable areas are crucial for understanding soil types and nutrient status, which in turn help to optimize crop yield and to design soil management strategies. This research aimed to characterize and classify soils in the Achewa small-scale irrigation area in Itang special district of southwest Gambella, Ethiopia. Representative pits were excavated at three slope locations, and soil profiles were examined and described directly in the field. To classify soil types, the WRB for Soil Resources guidelines were used. Across horizons, texture classes varied from clay loam to clay, whereas bulk density was within acceptable limits for mineral agricultural soils. Additionally, soil pH ranged from neutral to moderately alkaline. Organic matter content varied among topography positions, with values of 3.78%, 2.96%, and 2.85% at pedons 2 and 3 in the study area. Total nitrogen content was classified as low in pedon 3 and medium on the other two pedons, whereas available phosphorus content was classified as very high in all slope positions. Soil CEC and PBS were high and very high across all slope positions, with the dominant soluble cations being Calcium followed by magnesium, potassium, and sodium and extractable micronutrients (Fe, Mn, Zn, and Cu) were high to medium. Based on morphological, physical, and chemical analysis three soil types were identified: Eutric Fluvisols (Loamic), Pellic Vertisols (Gilgaic, Hypereutric), and Haplic Vertisols (Gilgaic). Therefore, implementing site-specific soil management techniques is recommended to enhance and sustain soil fertility and optimize crop and vegetable production, for ensuring long-term soil productivity in the study area.